Exploiting Unreduced Gametes for Improving Ornamental Plants - Xie, Li; Ke, Li-zhen; Lu, Xiao-qi; Chen, Jianjun; Zhang, Zhi-sheng (Frontiers in Plant Science, 2022)
The formation of gametes with somatic chromosome number or unreduced gametes (2n gametes) is an important process involved in the origin of polyploid plants in nature. Unreduced gametes are the result of meiotic mutations occurring during micro- and mega-sporogenesis. 2n gametes have been identified or artificially induced in a large number of plant species. Breeding of plants through 2n gametes can be advantageous because it combines genetic effects of polyploidy with meiotic recombination and sexual hybridization to produce tremendous genetic variation and heterosis. 2n gametes also occur in ornamental plants, but the potential of using 2n gametes in ornamental plant breeding has not been extensively exploited. Ornamental plants are primarily produced for their esthetic appearance and novelty, not for food and yield, and they can be readily propagated through vegetative means. Triploids, tetraploids, and plants with even higher ploidy levels produced through 2n gametes can be propagated through tissue culture to fix their phenotypes, thus leading to the development of new cultivars. In this review article, we intend to discuss the mechanisms underlying the formation of 2n gametes, techniques for 2n gamete identification, methods for enhancing 2n gamete formation, and the current status in the use of 2n gametes for development of novel ornamental plants. We believe that polyploidy breeding through 2n gametes represents a viable way of developing new cultivars, new species, and even new genera of ornamental plants.